Customer Perceived Brand Equity in Measuring Consumption Preference towards Local and Imported Products: A serial Studies on Urban and Suburban Level of Indonesia Society in Greater Jakarta - Rahayu, Sri (ASEAN Marketing Journal, 2021)
This study generally aims to analyze how the preferences of Indonesian as a customer in consuming local and imported products. The specific purpose of this study is to confirm measurement tools of the customer perceived brand equity, which are product country image, culture, marketing mix, and product quality. The result of this study indicates that Indonesian consider much about the marketing mix and product quality, while not so much considering culture.The product country image on the other hand gives the opposite effect. It is significantly related but has negative impact to the customer preference. This study is expected to provide insight on factors that contribute to form customer preference, consumption, and behavior in consuming local and imported product. It is expected that this study can bring impact in increasing local product competitiveness so that local and imported product could compete equally.